Risk Factors for Colonization with S.aureus and Methicillin Resistant Staphylococcus aureus Among Health Care Workers in Al-Batool teaching hospital for maternity and children in Diyala, Iraq - Mahjoob Aljboori, Mohamed; Abbas Abdul Jabbar , Rideh; Ibrahim Ali Al-Ezzy , Ali (Diyala Journal of Medicine, 2023)
Background: Staphylococcus aureus coloniza-tion for the human nose representing a challenge that requires a cope with host defense and competing resident microor-ganisms. Objective: To evaluate the risk factors for in-fection with S. au-reus and MRSA among health care workers (HCWs) in Al-Batool teaching hospital for maternity and children in Diyala, Iraq. Patients and Methods: A total of 27 swabs were taken from HCWs in Al-Batool teaching hospital for ma-ternity and chil-dren in Diyala, Iraq (ATHMC) Standard microbi-ological proce-dures were used for diagnosis of S. aureus and Methicillin Re-sistant Staphylo-coccus aureus (MRSA). Results: Significant corre-lation was report-ed between age and colonization with S. aureus & MRSA. Inverse correlation was reported between education level and colonization with S. aureus and MRSA. Signifi-cant correlation was reported be-tween acne and colonization with S. aureus. Signifi-cant correlation was reported be-tween sinusitis, years of experi-ence, contact with farm animals and colonization with S. aureus and MRSA. Significant correlation was reported between ward of duty and colonization with MRSA. Conclusion: Colonization with S. aureus and MRSA inversely correlated with younger age group, education level of HCWs. Colonization with S. aureus and MRSA correlated with sinusitis, years of experience (5 -6); contact with farm animals. Colonization with S. aureus correlated with acne. Colonization with MRSA correlated with ward of duty at children care floor.